Anatomical relationship between the common carotid artery and the internal jugular vein during head rotation. (May 2014) - Miki, Izumi; Murata, Satoru; Nakazawa, Ken; Onozawa, Shiro; Mine, Takahiko; Ueda, Tatsuo; Yamaguchi, Hidenori; Yasui, Daisuke; Takeda, Minako; Kumita, Shinichiro
This study investigated the anatomical relationship between the common carotid artery and internal jugular vein during head rotation for the effective performance of percutaneous transjugular procedures. The subjects included 30 volunteers who had never undergone internal jugular vein cannulation. In the supine position, two-dimensional ultrasonographic images of the right internal jugular vein and common carotid artery were obtained, 2 and 4 cm above the clavicle, along the lateral border of the sternal head of the sternocleidomastoid muscle. Ultrasonographic images were examined for head rotation at 0°, 15°, 30°, 45°, 60°, and 75° from the midline to the left. The percentage of overlap of the common carotid artery by the internal jugular vein and the flattening of the internal jugular vein at each head rotation position were measured and evaluated. The overlap of the common carotid artery by the internal jugular vein significantly increased at ≥45° of head rotation 2 cm above the clavicle (P < 0.01) and at ≥30° of head rotation 4 cm above the clavicle (P < 0.01), compared with that observed in the neutral position. The flattening of the internal jugular vein significantly decreased at ≥45° of head rotation 2 cm above the clavicle (P < 0.01) and at ≥30° of head rotation 4 cm above the clavicle (P < 0.01). Head rotation should be kept to <45° at 2 cm above the clavicle and <30° at 4 cm above the clavicle to decrease the risk of accidental puncture of the common carotid artery during internal jugular vein puncture. Moreover, flattening of the internal jugular vein gradually decreases during head rotation to the side.